Compositional domain structure in phosphatidylcholine--cholesterol and sphingomyelin--cholesterol bilayers. - Snyder, B (1980)
the lateral distribution of cholesterol in phospholipid bilayers has been investigated through a method of Monte Carlo calculations, using interaction energies deduced from calorimetric results for cholesterol-phospholipid mixtures. Analysis of computer-generated bilayer configurations allows calculation of the spatial localization and relative abundance of distinct regions of varying cholesterol content along the plane of the bilayer. An interfacial phospholipid region between cholesterol-bound and cholesterol-free domains is found to extend one lipid beyond the cholesterol-bound domain for mixtures of cholesterol with palmitoyl sphingomyelin, lignoceroyl sphingomyelin, and dipalmitoyl phosphatidylcholine. The results indicate that the degree of nonideality in the mixing of cholesterol is dependent on fatty acid chain length and that cholesterol mixes more ideally in sphingomyelins than in phosphatidylcholines of equal chain length. It is found that at approximately 20 mol % cholesterol the cholesterol-rich areas suddenly become connected, forming a network that extends over the entire bilayer. This change in the lateral connectivity of the cholesterol-rich domains occurs over a narrow concentration interval and is presumably responsible for the abrupt change in the lateral diffusion coefficient observed at this concentration.